Acknowledgements - Ntoumanis, Laura; Tolstopyat, Natalia (Satura, 2018)
The completion of this undertaking could not have been possible without the participation and support of so many people whose names may not all be enumerated. Their contributions are sincerely appreciated and gratefully acknowledged.